Method for preparing sodium ion battery hard carbon negative electrode material from biomass material

Through the washing, pre-carbonization and carbonization of biomass materials, combined with specific abrasive dispersants, the problem of low specific capacity and Coulomb efficiency of sodium ion battery hard carbon anode materials is solved, and higher sodium storage performance and economic benefits are achieved.

CN119284868APending Publication Date: 2025-01-10ANHUI XINNA MATERIAL SCIENCE & TECHNOLOGY CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411230537.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-02
Publication Date
2025-01-10

AI Technical Summary

Technical Problem

The specific capacity of existing sodium ion battery hard carbon anode materials is not high. For the first time, the Coulomb efficiency is poor and the process is complicated, resulting in poor economic benefits and difficult to achieve industrial production.

Method used

Methods for preparing sodium ion battery hard carbon anode material using biomass materials include washing, pre-carbonizing and carbonizing the biomass material in a washing solvent, combining bisoctadecylamine and ethanolamine thiol group through wet ball milling and high-temperature carbonization treatment. As a grinding dispersant, acetate enhances the interaction and stability of the materials and forms a larger closed-cell structure.

Benefits of technology

The specific capacity of sodium ion batteries has been improved, the first discharge and charging capacity has been significantly improved, and the Coulomb efficiency has been improved, achieving higher sodium storage performance and economic benefits.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005025985070000101
    Figure BDA0005025985070000101
Patent Text Reader

Abstract

The invention discloses a method for preparing a sodium-ion battery hard carbon negative electrode material from a biomass material, and relates to the field of sodium-ion battery negative electrode materials. According to the invention, dioctadecylamine and ethanolamine mercaptoacetate are connected to the surface of the hard carbon negative electrode material, and generated-CO-can form larger closed pores in the pyrolysis process. The hard carbon sample prepared by the method shows larger platform capacity (the first discharge specific capacity reaches 382mAh / g, and the first charge specific capacity reaches 359.46 mAh / g), and the sodium storage performance is improved, so that the specific capacity of the sodium ion battery is improved, and high coulombic efficiency is realized.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of sodium ion battery negative electrode materials, in particular to a method for preparing a sodium ion battery hard carbon negative electrode material from a biomass material. Background Art

[0002] Sodium-ion batteries first appeared in the early 1980s, but research on them stagnated as lithium-ion batteries performed better. After 2010, as the demand for power batteries grew, lithium-ion battery materials fell short of demand, and research on room-temperature sodium-ion batteries revived.

[0003] Unlike the graphite negative electrode used in lithium-ion batteries, the interlayer spacing of graphite is too small, and sodium ions with a larger radius need more energy to be embedded in the graphite interlayer, and cannot be reversibly deintercalated within the effective potential window. Therefore, it is believed that traditional graphite cannot be used as the negative electrode of sodium-ion batteries. The research directions of negative electrode materials for sodium-ion batteries include hard carbon, soft carbon, titanium-based oxides and alloys, with the most research on hard carbon. Currently, commercial sodium-ion batteries also mainly use hard carbon materials as negative electrodes.

[0004] The patent application with publication number CN116666585A discloses a sodium ion battery negative electrode material, a negative electrode sheet and a sodium ion battery, wherein the sodium ion battery comprises a negative electrode sheet; the negative electrode sheet comprises a current collector layer and a negative electrode material layer from the inside and the outside; wherein the negative electrode material layer is composed of a sodium ion battery negative electrode material and a binder; the sodium ion battery negative electrode material comprises crab shells, cystine and 4-nitrophthalonitrile; the crab shells are first crushed and ground, and pretreated with sodium hydroxide, and then cystine is added and carbonized to obtain a porous nitrogen and sulfur doped crab carbon material; the nitrogen and sulfur doped crab carbon material is then mixed with 4-nitrophthalonitrile to obtain a sodium ion battery negative electrode material.

[0005] The patent application with publication number CN116314587A discloses a sodium ion battery negative electrode sheet and a sodium ion battery. The sodium ion battery negative electrode sheet provided in the application comprises: a negative electrode current collector; a negative electrode active material layer coated on at least one surface of the negative electrode current collector; the negative electrode active material layer comprises the following composition in weight percentage: hard carbon 90-96%, conductive agent 1-3%, thickener 1-3%, binder 1-4%, liquid retaining agent 0.1-0.8%; and the hard carbon particle size distribution D50 (μm), tap density A (g / cm 3 ) and specific surface area B(m 2 / g) satisfies the following relationship: 3.O≤D50≤9.0, 0.1

[0006] ​The patent application with publication number CN113659143A discloses a method for preparing a negative electrode material for a sodium ion battery and a negative electrode material, a sodium ion battery. The patent application proposes a method for preparing a negative electrode material for a sodium ion battery, comprising: (1) a hydrothermal reaction of uniformly stirring phenylenediamine, tannic acid and graphene oxide in water, and then transferring the mixture into a reactor for hydrothermal reaction to obtain a composite; and (2) a carbonization reaction of carbonizing the composite in a carbonization furnace at 400 to 700°C.

[0007] In view of the above-mentioned public information and the hard carbon negative electrode materials prepared in the prior art, the specific capacity is not high and the first coulomb efficiency is poor. In addition, there are also problems such as complex process, which leads to poor economic benefits and difficulty in industrial production. Summary of the invention

[0008] The main purpose of the present invention is to provide a method for preparing a hard carbon negative electrode material for a sodium ion battery from a biomass material, so as to overcome the deficiencies in the prior art.

[0009] In order to achieve the above-mentioned object of the invention, the technical solution adopted by the present invention includes:

[0010] The present invention provides a method for preparing a hard carbon negative electrode material for a sodium ion battery from a biomass material, comprising the following steps:

[0011] Step 1: Wash 5-12 parts of biomass material in 30-60 parts of washing solvent for 1-3 hours, then wash with water until the pH is 7, and obtain a precursor material after drying;

[0012] Step 2: The precursor material obtained in step 1 is heated to 350-500° C. in a tube furnace for pre-carbonization for 1-3 hours, and after the pre-carbonization, the temperature is lowered to room temperature, and wet ball milled to obtain pre-carbonized powder;

[0013] Step 3: Carbonize the pre-carbonized powder obtained in step 2 in a tubular furnace at 1000-1400° C. for 1-5 hours, and cool to room temperature after carbonization to obtain a hard carbon negative electrode material for a sodium ion battery.

[0014] Preferably, in step one, the biomass material is selected from coconut shell activated carbon.

[0015] In some embodiments of the present invention, in step 1, the washing solvent is a mixture of hydrochloric acid solution and anhydrous ethanol, and the molar concentration of the hydrochloric acid solution is 0.5-1.2M.

[0016] The hydrochloric acid solution accounts for 30-60 wt % in the washing solvent.

[0017] Optionally, in step 2, the heating rate in the tubular furnace is 1-3°C / min; in step 3, the heating rate in the tubular furnace is 1-3°C / min, and the cooling rate is 2-4°C / min.

[0018] Wherein, in step 2, the wet ball milling condition parameters are: ball milling time is 2-5h, ball milling speed is 180-300rpm;

[0019] During wet ball milling, the pre-carbonized precursor material is ball milled with ball milling beads, grinding dispersant and organic solvent, and the mass ratio of the pre-carbonized precursor material, ball milling beads, grinding dispersant and organic solvent is 1:1.5-2.0:0.01-0.03:0.8-1.2.

[0020] The organic solvent may be anhydrous ethanol.

[0021] Preferably, the preparation method of the grinding dispersant comprises:

[0022] 10,13-epoxy-10,12-octadecadienoic acid undergoes coordination reaction with lanthanum nitrate to obtain 10,13-epoxy-10,12-octadecadienoic acid lanthanum;

[0023] Under alkaline conditions, the epoxy group of the obtained 10,13-epoxy-10,12-octadecadienoic acid lanthanum undergoes ring-opening reaction with the amino group in dioctadecylamine and the thiol group in ethanolamine thioglycolate, respectively, to obtain the grinding dispersant.

[0024] More preferably, the preparation method of the grinding dispersant is specifically as follows:

[0025] A1: 10-15 parts of 10,13-epoxy-10,12-octadecadienoic acid and 4-9 parts of lanthanum nitrate were mixed and added to a reactor, and 200-240 parts of water were added to the reactor, and the mixture was stirred at 50° C.-70° C. for 1-3 hours to obtain lanthanum 10,13-epoxy-10,12-octadecadienoate;

[0026] A2: 2-5 parts of 10,13-epoxy-10,12-octadecadienoic acid lanthanum, 0.2-2.5 parts of dioctadecylamine, 200-300 parts of ethanol, 5-9 parts of potassium hydroxide, stirring and reacting at 60-75° C. for 50-100 min, then adding 40-50 parts of ethanolamine thioglycolate, stirring and reacting at 60-70° C. for 50-100 min, and distilling off ethanol to obtain the grinding dispersant.

[0027] The amino group in dioctadecylamine undergoes a ring-opening reaction with the epoxy group in 10,13-epoxy-10,12-octadecadienoic acid lanthanum to form a stable nitrogen-oxygen bond, thereby connecting the dioctadecylamine to the surface of the hard carbon negative electrode material. The thiol group in ethanolamine thioglycolate undergoes a similar ring-opening reaction with the epoxy group in 10,13-epoxy-10,12-octadecadienoic acid lanthanum to form a sulfur-oxygen bond, connecting the ethanolamine thioglycolate to the surface of the hard carbon negative electrode material. These chemical reactions not only enhance the interaction between the dispersant and the hard carbon negative electrode material, but also help improve the stability and effectiveness of the dispersant during the grinding process. Preventing particle agglomeration ensures a more uniform and efficient grinding process.

[0028] During the pyrolysis process, the generated -CO- produces narrower and longer graphite crystallites, resulting in larger closed pores.

[0029] In some embodiments of the present invention, high-purity nitrogen is continuously introduced during the entire process of step 2 and step 3, and the gas flow rate is 10-50cc / min.

[0030] The present invention also provides a sodium ion battery negative electrode sheet, comprising a negative electrode material, wherein the negative electrode material is the sodium ion battery hard carbon negative electrode material prepared by the above method.

[0031] The present invention also provides a sodium ion battery, wherein the counter electrode of the sodium ion battery is metallic sodium, the diaphragm is a glass fiber membrane, and the negative electrode sheet is the negative electrode sheet of the sodium ion battery described above.

[0032] Beneficial effects of the present invention:

[0033] The present invention connects dioctadecylamine and ethanolamine thioglycolate to the surface of the hard carbon negative electrode material, and during the pyrolysis process, the generated -CO- will form larger closed pores. The hard carbon sample prepared by the present invention exhibits a larger platform capacity (the first discharge specific capacity reaches 382mAh / g, and the first charge specific capacity reaches 359.46mAh / g), improves the sodium storage performance, thereby improving the specific capacity of the sodium ion battery and achieving high coulombic efficiency. DETAILED DESCRIPTION

[0034] The technical solution, implementation process and principle of the present invention will be further explained as follows.

[0035] Example 1

[0036] The preparation method of the grinding dispersant used in this embodiment is:

[0037] A1: 10 g of 10,13-epoxy-10,12-octadecadienoic acid and 4 g of lanthanum nitrate were mixed and added to a reactor, and 200 g of water was added to the reactor. The mixture was stirred at 50° C. for 1 h, and dried to remove water to obtain 10,13-epoxy-10,12-octadecadienoic acid lanthanum;

[0038] A2: 2 g of 10,13-epoxy-10,12-lanthanum octadecadienoate, 0.2 g of dioctadecylamine, 200 g of ethanol and 5 g of potassium hydroxide were mixed, stirred at 60° C. for 50 minutes, 40 g of ethanolamine thioglycolate was added, stirred at 60° C. for 50 minutes, and the ethanol was distilled off to obtain a grinding dispersant.

[0039] In this embodiment, a method for preparing a hard carbon negative electrode material for a sodium ion battery from a biomass material is described, and the operation steps are as follows:

[0040] Step 1: Stir and wash 5 g of coconut shell activated carbon in a mixture of 30 g of hydrochloric acid solution and anhydrous ethanol (the molar concentration of hydrochloric acid is 0.5 M, and the hydrochloric acid solution accounts for 60 wt % in the mixture) for 1 h, then wash with deionized water to a pH of 7, and dry to obtain a precursor material;

[0041] Step 2: The precursor material prepared in step 1 is heated to 350°C in a tube furnace at a rate of 3°C / min for pre-carbonization for 1 hour. After the pre-carbonization, the temperature is cooled to room temperature at a cooling rate of 4°C / min, and wet-milled at a ball mill speed of 180 rpm for 2 hours to obtain pre-carbonized powder;

[0042] Among them, the mass ratio of the pre-carbonized precursor material, ball milling beads, grinding dispersant, and anhydrous ethanol is 1:1.5:0.01:0.8;

[0043] Step 3: The pre-carbonized powder obtained in step 2 is heated to 1000°C in a tubular furnace at a heating rate of 3°C / min for high-temperature carbonization for 5 hours. After carbonization, the temperature is cooled to room temperature at a cooling rate of 4°C / min to obtain a hard carbon negative electrode material for a sodium ion battery.

[0044] High-purity nitrogen was continuously introduced during the entire process of step 2 and step 3, and the gas flow rate was 10 cc / min.

[0045] Example 2

[0046] The preparation method of the grinding dispersant used in this embodiment is:

[0047] A1: 12 g of 10,13-epoxy-10,12-octadecadienoic acid and 6 g of lanthanum nitrate were mixed and added to a reactor, and 220 g of water was added to the reactor. The mixture was stirred at 60° C. for 2 h, and dried to remove water to obtain 10,13-epoxy-10,12-octadecadienoic acid lanthanum;

[0048] A2: 3 g of 10,13-epoxy-10,12-lanthanum octadecadienoate, 0.8 g of dioctadecylamine, 235 g of ethanol and 6 g of potassium hydroxide were mixed, stirred at 65° C. for 60 minutes, and then 45 g of ethanolamine thioglycolate was added, stirred at 65° C. for 65 minutes, and the ethanol was distilled off to obtain a grinding dispersant.

[0049] In this embodiment, a method for preparing a hard carbon negative electrode material for a sodium ion battery from a biomass material is described, and the operation steps are as follows:

[0050] Step 1: Stir and wash 7 g of coconut shell activated carbon in a mixture of 40 g of hydrochloric acid solution and anhydrous ethanol (the molar concentration of hydrochloric acid is 0.8 M, and the hydrochloric acid solution accounts for 50 wt % in the mixture) for 2 h, then wash with deionized water to a pH of 7, and dry to obtain a precursor material;

[0051] Step 2: The precursor material prepared in step 1 is heated to 400°C in a tube furnace at a rate of 2°C / min for pre-carbonization for 2h. After the pre-carbonization, the temperature is lowered to room temperature at a rate of 3°C / min, and wet-milled at a ball mill speed of 220rpm for 3h to obtain pre-carbonized powder;

[0052] Among them, the mass ratio of the pre-carbonized precursor material, ball milling beads, grinding dispersant, and anhydrous ethanol is 1:1.6:0.02:1;

[0053] Step 3: The pre-carbonized powder obtained in step 2 is heated to 1200°C at a rate of 2°C / min in a tubular furnace for high-temperature carbonization for 3 hours. After carbonization, the temperature is cooled to room temperature at a rate of 3°C / min to obtain a hard carbon negative electrode material for a sodium ion battery.

[0054] High-purity nitrogen is continuously introduced during the entire process of step 2 and step 3, and the gas flow rate is 25cc / min.

[0055] Example 3

[0056] The preparation method of the grinding dispersant used in this embodiment is:

[0057] A1: 14 g of 10,13-epoxy-10,12-octadecadienoic acid and 8 g of lanthanum nitrate were mixed and added to a reactor, and 220 g of water was added to the reactor. The mixture was stirred at 60° C. for 2 h, and dried to remove water to obtain 10,13-epoxy-10,12-octadecadienoic acid lanthanum;

[0058] A2: 4 g of 10,13-epoxy-10,12-lanthanum octadecadienoate, 1.6 g of dioctadecylamine, 280 g of ethanol and 8 g of potassium hydroxide were mixed, stirred at 70° C. for 80 minutes, and then 45 g of ethanolamine thioglycolate was added, stirred at 65° C. for 80 minutes, and the ethanol was distilled off to obtain a grinding dispersant.

[0059] In this embodiment, a method for preparing a hard carbon negative electrode material for a sodium ion battery from a biomass material is described, and the operation steps are as follows:

[0060] Step 1: Stir and wash 10 g of coconut shell activated carbon in a mixture of 50 g of hydrochloric acid solution and anhydrous ethanol (the molar concentration of hydrochloric acid is 1 M, and the hydrochloric acid solution accounts for 40 wt % in the mixture) for 2 h, then wash with deionized water to a pH of 7, and dry to obtain a precursor material;

[0061] Step 2: The precursor material prepared in step 1 is heated to 450°C in a tube furnace at a rate of 2°C / min for pre-carbonization for 2 hours. After the pre-carbonization, the temperature is lowered to room temperature at a rate of 3°C / min, and wet-milled at a ball mill speed of 260 rpm for 4 hours to obtain pre-carbonized powder;

[0062] Among them, the mass ratio of the pre-carbonized precursor material, ball milling beads, grinding dispersant, and anhydrous ethanol is 1:2:0.03:1;

[0063] Step 3: The pre-carbonized powder obtained in step 2 is heated to 1300°C at a rate of 2°C / min in a tubular furnace for high-temperature carbonization for 2 hours. After carbonization, the temperature is cooled to room temperature at a rate of 3°C / min to obtain a hard carbon negative electrode material for a sodium ion battery.

[0064] High-purity nitrogen is continuously introduced during the entire process of step 2 and step 3, and the gas flow rate is 40cc / min.

[0065] Example 4

[0066] The preparation method of the grinding dispersant used in this embodiment is:

[0067] A1: 15 g of 10,13-epoxy-10,12-octadecadienoic acid and 9 g of lanthanum nitrate were mixed and added to a reactor, and 240 g of water was added to the reactor. The mixture was stirred at 70° C. for 3 h, and dried to remove water to obtain 10,13-epoxy-10,12-octadecadienoic acid lanthanum;

[0068] A2: 5 g of 10,13-epoxy-10,12-lanthanum octadecadienoate, 2.5 g of dioctadecylamine, 300 g of ethanol and 9 g of potassium hydroxide were mixed, stirred at 75° C. for 100 minutes, and then 50 g of ethanolamine thioglycolate was added, stirred at 70° C. for 100 minutes, and the ethanol was distilled off to obtain a grinding dispersant.

[0069] In this embodiment, a method for preparing a hard carbon negative electrode material for a sodium ion battery from a biomass material is described, and the operation steps are as follows:

[0070] Step 1: Stir and wash 12 g of coconut shell activated carbon in a mixture of 60 g of hydrochloric acid solution and anhydrous ethanol (the molar concentration of hydrochloric acid is 1.2 M, and the hydrochloric acid solution accounts for 60 wt % in the mixture) for 3 h, then wash with deionized water to a pH of 7, and dry to obtain a precursor material;

[0071] Step 2: The precursor material prepared in step 1 was heated to 500°C in a tube furnace at a rate of 1°C / min for pre-carbonization for 3 hours. After the pre-carbonization, the temperature was lowered to room temperature at a rate of 2°C / min, and wet-milled at a ball mill speed of 300 rpm for 5 hours to obtain a pre-carbonized powder;

[0072] Among them, the mass ratio of the pre-carbonized precursor material, ball milling beads, grinding dispersant, and anhydrous ethanol is 1:1.8:0.03:1.2;

[0073] Step 3: The pre-carbonized powder obtained in step 2 is heated to 1400°C at a rate of 1°C / min in a tubular furnace for high-temperature carbonization for 1 hour. After carbonization, the temperature is cooled to room temperature at a rate of 2°C / min to obtain a hard carbon negative electrode material for a sodium ion battery.

[0074] High-purity nitrogen is continuously introduced during the entire process of step 2 and step 3, and the gas flow rate is 50cc / min.

[0075] Comparative Example 1

[0076] In this comparative example, a method for preparing a hard carbon negative electrode material for a sodium ion battery from a biomass material is provided, and the operating steps are as follows:

[0077] Step 1: Stir and wash 5 g of coconut shell activated carbon in a mixture of 30 g of hydrochloric acid solution and anhydrous ethanol (the molar concentration of hydrochloric acid is 0.5 M, and the hydrochloric acid solution accounts for 60 wt % in the mixture) for 1 h, then wash with deionized water to a pH of 7, and dry to obtain a precursor material;

[0078] Step 2: The precursor material prepared in step 1 is heated to 350°C in a tube furnace at a rate of 3°C / min for pre-carbonization for 1 hour. After the pre-carbonization, the temperature is lowered to room temperature at a rate of 4°C / min, and wet-milled at a ball mill speed of 180 rpm for 2 hours to obtain pre-carbonized powder;

[0079] Among them, the mass ratio of the pre-carbonized precursor material, ball milling beads, and anhydrous ethanol is 1:1.5:0.8;

[0080] Step 3: The pre-carbonized powder obtained in step 2 is heated to 1000°C at a rate of 3°C / min in a tubular furnace for high-temperature carbonization for 5 hours. After carbonization, the temperature is cooled to room temperature at a rate of 4°C / min to obtain a hard carbon negative electrode material for a sodium ion battery.

[0081] High-purity nitrogen gas was continuously introduced during the entire process of step 2 and step 3, and the gas flow rate was 10 cc / min.

[0082] Comparative Example 2

[0083] The preparation method of the grinding dispersant used in this comparative example is:

[0084] A1: 10 g of 10,13-epoxy-10,12-octadecadienoic acid and 4 g of lanthanum nitrate were mixed and added to a reactor, and 200 g of water was added to the reactor. The mixture was stirred at 50° C. for 1 h, and dried to remove water to obtain 10,13-epoxy-10,12-octadecadienoic acid lanthanum;

[0085] A2: 2 g of 10,13-epoxy-10,12-lanthanum octadecadienoate, 200 g of ethanol and 5 g of potassium hydroxide were mixed, stirred at 60° C. for 50 minutes, and then 40 g of ethanolamine thioglycolate was added, stirred at 60° C. for 50 minutes, and the ethanol was distilled off to obtain a grinding dispersant.

[0086] In this comparative example, a method for preparing a hard carbon negative electrode material for a sodium ion battery from a biomass material is provided, and the operating steps are as follows:

[0087] Step 1: Stir and wash 5 g of coconut shell activated carbon in a mixture of 30 g of hydrochloric acid solution and anhydrous ethanol (the molar concentration of hydrochloric acid is 0.5 M, and the hydrochloric acid solution accounts for 60 wt % in the mixture) for 1 h, then wash with deionized water to a pH of 7, and dry to obtain a precursor material;

[0088] Step 2: The precursor material prepared in step 1 is heated to 350°C in a tube furnace at a rate of 3°C / min for pre-carbonization for 1 hour. After the pre-carbonization, the temperature is lowered to room temperature at a rate of 4°C / min, and wet-milled at a ball mill speed of 180 rpm for 2 hours to obtain pre-carbonized powder;

[0089] Among them, the mass ratio of the pre-carbonized precursor material, ball milling beads, grinding dispersant, and anhydrous ethanol is 1:1.5:0.01:0.8;

[0090] Step 3: The pre-carbonized powder obtained in step 2 is heated to 1000°C at a rate of 3°C / min in a tubular furnace for high-temperature carbonization for 5 hours. After carbonization, the temperature is cooled to room temperature at a rate of 4°C / min to obtain a hard carbon negative electrode material for a sodium ion battery.

[0091] High-purity nitrogen gas was continuously introduced during the entire process of step 2 and step 3, and the gas flow rate was 10 cc / min.

[0092] Comparative Example 3

[0093] The preparation method of the grinding dispersant used in this comparative example is:

[0094] A1: 10 g of 10,13-epoxy-10,12-octadecadienoic acid and 4 g of lanthanum nitrate were mixed and added to a reactor, and 200 g of water was added to the reactor. The mixture was stirred at 50° C. for 1 h, and dried to remove water to obtain 10,13-epoxy-10,12-octadecadienoic acid lanthanum;

[0095] A2: 2 g of 10,13-epoxy-10,12-lanthanum octadecadienoate, 0.2 g of dioctadecylamine, 200 g of ethanol and 5 g of potassium hydroxide were mixed, stirred at 60° C. for 100 minutes, stirred at 60° C. for 50 minutes, and the ethanol was distilled off to obtain a grinding dispersant.

[0096] In this comparative example, a method for preparing a hard carbon negative electrode material for a sodium ion battery from a biomass material is provided, and the operating steps are as follows:

[0097] Step 1: Stir and wash 5 g of coconut shell activated carbon in a mixture of 30 g of hydrochloric acid solution and anhydrous ethanol (the molar concentration of hydrochloric acid is 0.5 M, and the hydrochloric acid solution accounts for 60 wt % in the mixture) for 1 h, then wash with deionized water to a pH of 7, and dry to obtain a precursor material;

[0098] Step 2: The precursor material prepared in step 1 is heated to 350°C in a tube furnace at a rate of 3°C / min for pre-carbonization for 1 hour. After the pre-carbonization, the temperature is lowered to room temperature at a rate of 4°C / min, and wet-milled at a ball mill speed of 180 rpm for 2 hours to obtain pre-carbonized powder;

[0099] Among them, the mass ratio of the pre-carbonized precursor material, ball milling beads, grinding dispersant, and anhydrous ethanol is 1:1.5:0.01:0.8;

[0100] Step 3: The pre-carbonized powder obtained in step 2 is heated to 1000°C at a rate of 3°C / min in a tubular furnace for high-temperature carbonization for 5 hours. After carbonization, the temperature is cooled to room temperature at a rate of 4°C / min to obtain a hard carbon negative electrode material for a sodium ion battery.

[0101] High-purity nitrogen gas was continuously introduced during the entire process of step 2 and step 3, and the gas flow rate was 10 cc / min.

[0102] Test Example 1

[0103] The hard carbon negative electrode material powder for sodium ion battery prepared in the above examples and comparative examples was mixed with conductive carbon black, and the mass ratio of hard carbon negative electrode material, conductive carbon black and sodium carboxymethyl cellulose (CMC) was 18:1:1. Then the obtained mixture was added into CMC aqueous solution and stirred for 6 hours, and then coated on carbon-coated aluminum foil to prepare negative electrode sheet. Then, a metal sodium sheet was used as a counter electrode, and NaClO 4 The electrolyte is a mixture of ethylene carbonate / diethyl carbonate. In the electrolyte, NaClO 4 The concentration was 1 mol / L, the mass ratio of ethylene carbonate / diethyl carbonate was 1:1, and GF / C glass fiber film (brand: whatman) was used as the separator to assemble a 2016 type button battery.

[0104] When the battery charge and discharge current is 30 mA / g, the electrical performance test results are shown in Table 1.

[0105] Table 1

[0106]

[0107] From the test results in Table 1, it can be seen that the hard carbon sample prepared by the present invention exhibits a larger platform capacity (the first discharge specific capacity reaches 382 mAh / g, and the first charge specific capacity reaches 359.46 mAh / g), which improves the sodium storage performance, thereby improving the specific capacity of the sodium ion battery and achieving high coulombic efficiency.

[0108] It should be understood that the above embodiments are only for illustrating the technical concept and features of the present invention, and their purpose is to enable people familiar with the technology to understand the content of the present invention and implement it accordingly, and they cannot be used to limit the protection scope of the present invention. Any equivalent changes or modifications made according to the spirit of the present invention should be included in the protection scope of the present invention.

Claims

1. A method for preparing a hard carbon negative electrode material for a sodium ion battery from biomass materials, characterized in that: The following steps are involved: Step 1: Wash 5-12 parts of biomass material in 30-60 parts of washing solvent for 1-3 hours, then wash with water until the pH is 7, and obtain a precursor material after drying; Step 2: The precursor material obtained in step 1 is heated to 350-500° C. in a tube furnace for pre-carbonization for 1-3 hours, and after the pre-carbonization, the temperature is lowered to room temperature, and wet ball milled to obtain pre-carbonized powder; Step 3: Carbonize the pre-carbonized powder obtained in step 2 in a tubular furnace at 1000-1400° C. for 1-5 hours, and cool to room temperature after carbonization to obtain the sodium ion battery hard carbon negative electrode material.

2. The method for preparing hard carbon negative electrode materials for sodium ion batteries from biomass materials according to claim 1, characterized in that: In step one, the biomass material is selected from coconut shell activated carbon.

3. The method for preparing hard carbon negative electrode materials for sodium ion batteries from biomass materials according to claim 1, characterized in that: In step 1, the washing solvent is a mixture of hydrochloric acid solution and anhydrous ethanol. The molar concentration of the hydrochloric acid solution is 0.5-1.2M, The hydrochloric acid solution accounts for 30-60 wt % in the washing solvent.

4. The method for preparing hard carbon negative electrode materials for sodium ion batteries from biomass materials according to claim 1, characterized in that: In step 2 and step 3, the heating rate in the tubular furnace is 1-3°C / min, and the cooling rate is 2-4°C / min.

5. The method for preparing hard carbon negative electrode materials for sodium ion batteries from biomass materials according to claim 1, characterized in that: In step 2, the wet ball milling conditions are as follows: the ball milling time is 2-5 hours, and the ball milling speed is 180-300 rpm; During wet ball milling, the pre-carbonized precursor material is ball milled with ball milling beads, grinding dispersant and organic solvent, and the mass ratio of the pre-carbonized precursor material, ball milling beads, grinding dispersant and organic solvent is 1:1.5-2.0:0.01-0.03:0.8-1.

2.

6. The method for preparing hard carbon negative electrode materials for sodium ion batteries from biomass materials according to claim 5, characterized in that: The preparation method of the grinding dispersant comprises: 10,13-epoxy-10,12-octadecadienoic acid undergoes coordination reaction with lanthanum nitrate to obtain 10,13-epoxy-10,12-octadecadienoic acid lanthanum; Under alkaline conditions, the epoxy group of the obtained 10,13-epoxy-10,12-octadecadienoic acid lanthanum undergoes ring-opening reaction with the amino group in dioctadecylamine and the thiol group in ethanolamine thioglycolate, respectively, to obtain the grinding dispersant.

7. The method for preparing hard carbon negative electrode materials for sodium ion batteries from biomass materials according to claim 6, characterized in that: The preparation method of the grinding dispersant is specifically as follows: A1: 10-15 parts of 10,13-epoxy-10,12-octadecadienoic acid and 4-9 parts of lanthanum nitrate were mixed and added to a reactor, and 200-240 parts of water were added to the reactor, and the mixture was stirred at 50° C.-70° C. for 1-3 hours to obtain lanthanum 10,13-epoxy-10,12-octadecadienoate; A2: 2-5 parts of 10,13-epoxy-10,12-octadecadienoic acid lanthanum, 0.2-2.5 parts of dioctadecylamine, 200-300 parts of ethanol, 5-9 parts of potassium hydroxide, stirring and reacting at 60-75° C. for 50-100 min, then adding 40-50 parts of ethanolamine thioglycolate, stirring and reacting at 60-70° C. for 50-100 min, and distilling off ethanol to obtain the grinding dispersant.

8. The method for preparing hard carbon negative electrode materials for sodium ion batteries from biomass materials according to claim 1, characterized in that: Nitrogen is continuously introduced during the entire process of step 2 and step 3, with a gas flow rate of 10-50cc / min.

9. A sodium ion battery negative electrode sheet, characterized in that: The invention comprises a negative electrode material, wherein the negative electrode material is a hard carbon negative electrode material for a sodium ion battery prepared by the method according to any one of claims 1 to 8.

10. A sodium ion battery, characterized in that: The counter electrode of the sodium ion battery is metallic sodium, the separator is a glass fiber membrane, and the negative electrode sheet is the negative electrode sheet of the sodium ion battery according to claim 9.

Citation Information

Patent Citations

  • Preparation method of sodium ion battery negative electrode material, negative electrode material and sodium ion battery

    CN113659143A

  • Sodium ion battery negative plate and sodium ion battery

    CN116314587A

  • Sodium-ion battery negative electrode material, negative electrode plate and sodium-ion battery

    CN116666585A